GAMIFICATION OF CIVIC EDUCATION BASED ON TRADITIONAL FAHOMBO FIGHTING VALUES IN DEVELOPING A PERSEVERANT CHARACTE - Darmawan Harefa (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to analyze the effectiveness of gamification in Civics Education (PPKn) based on the traditional Fahombo fighting values in developing a perseverant character among high school students in South Nias Regency. The gamification model was developed by integrating the symbolism of the Fahombo stone-jumping tradition as a metaphor for challenge, courage, and mental resilience, making PPKn learning not only theoretical but also contextual and culturally relevant. The research method employed was a library research and literature review, supported by observations of gamification implementation in several high schools in South Nias. The findings indicate that gamification based on Fahombo traditional values enhances students’ learning motivation, engagement, as well as critical and collaborative thinking skills. Furthermore, this approach effectively fosters a perseverant character, encouraging students to keep trying despite initial failures. This study confirms that integrating local wisdom into PPKn gamification can serve as an innovative strategy for character education, strengthen cultural identity, and instill Pancasila values meaningfully. These findings also provide opportunities for the development of a more contextual and culturally grounded curriculum in secondary schools.